Sensory and nutritional evaluation of nine types of millet substituted for polished white rice in select Indian meal preparations - Anitha, Seetha; Arjun, Priya; Palli, Nagarekha C.; Sreekanth, N.; Miruthika Devi, S. A.; Pandey, Sangeeta; Krishnan, Sridhar; Prasad, Shyam; Sharma, Shashi; Chidambara Murthy, K. N.; Botha, Rosemary; Upadhyay, Shweta; et al. (Frontiers in Sustainable Food Systems, 2024)
This study was conducted to test the suitability of using nine types of millets namely finger millet, pearl millet, white and yellow sorghum, little millet, barnyard millet, proso millet, kodo millet and browntop millet in seven popular Indian dishesmeal preparations based on sensory characteristics and nutrient value. The popular Indian dishesmeal preparations tested were boiled grain, dosa, idli, bisibele bathbisi belle bath, pulao, puttu, and pongal. In total, 53 variations in dishesmeal preparations were developed using the millets and 7 refined ricepolished white rice-based dishesmeal preparations were developed as control. The main findings indicated that meal preparation crafted from various millets garnered overall sensory scores closely resembling to those derived from refinedpolished white rice. Notably, little millet exhibited high scores in pongal, and millet dosa, and achieved elevated overall sensory scores compared to meal preparation from polished white rice. The results showed that all seven dishes made with different millets had overall sensory scores almost close to those of dishes made from refined rice. while little millet scored high in pongal and millets dosa in general had a high overall sensory score compared to refined rice. Bisibele bathBisi belle bath made of barnyard millet scored higher in overall sensory score than refined ricepolished white rice. Moreover, there was significant association between some types of millets' overall sensory characteristics (p <0.005) with refined ricepolished white rice-based dishesmeal preparations. In terms of nutrient value, all the millet-based dishesmeal preparations had significantly high nutritional value compared to those made with refined ricepolished white rice (p <0.005). Especially calcium content of the meal prepared with finger millet was